Magnetic resonance imaging for groundwater - Legchenko, Anatoly (Focus nanoscience and nanotechnology series., 2013)
This book presents the basics of the non-invasive geophysical method for groundwater investigation, called Magnetic Resonance Sounding (MRS) or Surface Nuclear Magnetic Resonance (SNMR), and its practical application to the problems of groundwater localization and aquifer characterization. The method is based on the nuclear magnetic resonance (NMR) phenomenon and is selectively sensitive to groundwater. The main aims of the author are to teach the reader the basic principles of the method as well as to formulate consistent approximate models, leading to reasonably simple inverse problems.